2012
DOI: 10.1371/journal.pone.0052754
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Progression Mediated by Horizontal Gene Transfer in an In Vivo Model

Abstract: It is known that cancer progresses by vertical gene transfer, but this paradigm ignores that DNA circulates in higher organisms and that it is biologically active upon its uptake by recipient cells. Here we confirm previous observations on the ability of cell-free DNA to induce in vitro cell transformation and tumorigenesis by treating NIH3T3 recipient murine cells with serum of colon cancer patients and supernatant of SW480 human cancer cells. Cell transformation and tumorigenesis of recipient cells did not o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
109
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(128 citation statements)
references
References 38 publications
5
109
0
6
Order By: Relevance
“…A study by Garcia-Olmo et al (2010) have demonstrated the potential of plasma DNA to transfect and oncogenically transform susceptible cells, and showed that plasma of colon cancer patient selectively transforms NIH/3T3 mouse cells while having no effect on human adipose-derived stem cells. Similar findings were also reported by Trejo-Becerril et al (2012) in an in vivo immunocompetent coloncarcinogenesis rat model. However, a number of observations have limited the validity of this hypothesis.…”
Section: Origin Of Ctdnasupporting
confidence: 90%
“…A study by Garcia-Olmo et al (2010) have demonstrated the potential of plasma DNA to transfect and oncogenically transform susceptible cells, and showed that plasma of colon cancer patient selectively transforms NIH/3T3 mouse cells while having no effect on human adipose-derived stem cells. Similar findings were also reported by Trejo-Becerril et al (2012) in an in vivo immunocompetent coloncarcinogenesis rat model. However, a number of observations have limited the validity of this hypothesis.…”
Section: Origin Of Ctdnasupporting
confidence: 90%
“…It has also been suggested, that another important function of the DNaseI-based mechanism of clearing cfDNA from human blood is the prevention of autoimmunity against DNA (47). Involvement of cfDNA was suggested for other biological processes as well, ranging from tumor dissemination (2,(48)(49)(50) to aging (51), but experimental evidence supporting such hypotheses remains tenuous, and considerable additional research is needed to clarify the involvement of cfDNA in processes other than immunologic response.…”
Section: Biological Role Of Cfdnamentioning
confidence: 99%
“…To date, there is no direct evidence that mutated cirDNA can initiate metastases. However, studies later confirmed that cirDNA (k-ras codon 12 mutated DNA) can promote tumor progression via lateral gene transfer (LGT) in rats that already have developed tumors, but does not itself initiate tumor formation in the host animal [117]. This concept of tumorigenic DNA being involved in cancer metastasis correlates so effectively with Darwin's gemmules that one cannot help but agree with Liu [118] that gemmules are analogues to cirNAs.…”
Section: The Concept Of Transcessionmentioning
confidence: 95%